Contraceptive Use in East Timorese Ex-Refugee Women in Indonesia: Determinants and Barriers - Nahak, Maria Paula Marla; Meo, Maria Lupita Nena; Simon, Maria Getrida (Journal of Maternal and Child Health, 2020)
Background: Poor access to contraceptive services is a global health problem, especially in the marginal community order. Refugee camps and areas with weak community order are the groups with the lowest prevalence of contra